The Avengers, Earth's mightiest heroes. Volume 3, Iron man unleashed [videorecording (DVD)]. - Loomis, Eric, 1964-; O'Shaughnessey, Colleen; Wasserman, Rick; Tatasciore, Fred; Bloom, Brian, 1970- (Marvel DVD super hero collection., 2011)
After 74 villains break out of prison, Marvel's most powerful superheroes team up to capture all of them, and also to defend the Earth from widespread threats.